Role of Asleep Surgery for Supplementary Motor Area Tumors - Krishna Kumar G; Chandrasekhar Chigurupalli; Anandh Balasubramaniam; B. J. Rajesh; Nitin Manohar (Indian Journal of Neurosurgery)
Background The supplementary motor area (SMA) is involved in planning of voluntary motor activities. Tumors in SMA usually present with seizures and, rarely, motor deficits. Postoperatively, these patients may develop SMA syndrome. Patients with SMA tumors usually undergo awake craniotomy along with neuromonitoring for maximal safe resection, and some of these patients tend to have residual tumor.